Analisis Kesesuaian Perencanaan Audit Laporan Keuangan Dengan Standar Profesional Akuntan Publik (Studi Pada Kap Di Wilayah Malang) - Brillianti Alifia Az Zahra (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Audit planning is one of the determining factors for the success of an audit. Therefore, this stage requires special attention from KAP in order to determine a quality audit plan. To ensure this, audit planning by KAP can be guided by the Audit Standards (SA) in the Public Accountant Professional Standards (SPAP). The object of this research is one of the KAPs in the Malang area. This research aims to analyze the suitability of the audit planning carried out by KAP ABC with SPAP. The method used is descriptive analysis with a qualitative approach. Data was obtained through interviews with one of the auditor staff and observations made by the author during his internship at the KAP. The research results show that the financial report audit planning of KAP ABC is in accordance with the SPAP Audit Planning.